Thomas Pynchon and Don DeLillo as Elders - Grgas-Mufa, Stipe (2011)
The article explores the implications of teaching and reading Pynchon and DeLillo if we approach their texts with the knowledge that both of them are now in their seventies.
Projekt MZOS
ENG